Assessment of a natural grass carp reovirus genotype II avirulent strain GD1108 shows great potential as an avirulent live vaccine. (March 2021) - Gao, Caixia; Wang, Yingying; Hu, Huzi; Zhou, Wenli; Yin, Jiyuan; Li, Yingying; Bergmann, Sven M.; Wu, Siyu; Zeng, Weiwei; Wang, Qing
Abstract: Vaccine immunization is currently the only effective way to prevent and control the grass carp haemorrhagic disease, and the primary pathogen in these infections is grass carp reovirus genotype II (GCRV-II) for which there is no commercial vaccine. In this study, we evaluated the safety of the GCRV-II avirulent strain GD1108 which isolated in the early stage of the laboratory through continuously passed in grass carp. The immunogenicity and protective effects were evaluated after immunization by injection and immersion. The avirulent strain GD1108 could infect and replicate in the fish which did not revert to virulence after continuous passage. No adverse side effects were observed and the vaccine strain did not spread horizontally among fish. Two routes of immunization induced high serum antibody titers of OD450nm value were 0.79 and 0.76 and neutralization titers of 320 and 320 for the injection and immersion routes of inoculation, respectively. The expression of immune-related genes increased after immunization and the levels were statistically significant. Challenge of immunized fish with a virulent GCRV-II strain resulted in protection rates of 93.88% and 76.00% for the injection and immersion routes, respectively. The avirulent strain GD1108 revealed good safety and immunogenicity via two different inoculation routes. Although the injection route provided the best immune effect, two pathways provided protection against infection with virulent GCRV-II strains in various degrees. These results indicated that the avirulent strain GD1108 can be used for the development and application as live vaccine. Highlights: The avirulent strain GD1108 was used as an avirulent live vaccine candidate after safety evaluation. The immunogenicity and protective effects of the avirulent vaccine were evaluated by two different inoculation pathways. The avirulent vaccine GD1108 conferred a maximum RPS of 93.88% against challenge with virulent GCRV-II. The avirulent live vaccine might provide an effective method of coping with GCRV-II disease.